2022
DOI: 10.3389/fneur.2022.923206
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Ventricular primary central nervous system lymphoma with partial hypointensity on diffusion-weighted imaging

Abstract: IntroductionPrimary central nervous system lymphoma (PCNSL) is infrequent and represents 3. 1% of primary brain tumors. And the lesions that are restricted to the ventricular system, particularly the third ventricle, are even rarer. There are few pieces of literature or case reports to date. We report a case of PCNSL with partial hypointense on diffusion-weighted imaging (DWI) located in the lateral and third ventricles. Then we reviewed almost all case reports of ventricular PCNSLs in the last 20 years, discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[25] Intracerebroventricular PCNSL is mainly located in the lateral ventricles and the third and fourth ventricles. [26,27] In 2013, Cheatle et al [28] reported a case of PCNSL originating from the septum pellucidum in a young woman. Isolated PCNSL in the septum pellucidum has been rarely reported in immunocompetent elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Intracerebroventricular PCNSL is mainly located in the lateral ventricles and the third and fourth ventricles. [26,27] In 2013, Cheatle et al [28] reported a case of PCNSL originating from the septum pellucidum in a young woman. Isolated PCNSL in the septum pellucidum has been rarely reported in immunocompetent elderly patients.…”
Section: Introductionmentioning
confidence: 99%